6(x+5)+2=-6(x-7)-9

Simple and best practice solution for 6(x+5)+2=-6(x-7)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+5)+2=-6(x-7)-9 equation:


Simplifying
6(x + 5) + 2 = -6(x + -7) + -9

Reorder the terms:
6(5 + x) + 2 = -6(x + -7) + -9
(5 * 6 + x * 6) + 2 = -6(x + -7) + -9
(30 + 6x) + 2 = -6(x + -7) + -9

Reorder the terms:
30 + 2 + 6x = -6(x + -7) + -9

Combine like terms: 30 + 2 = 32
32 + 6x = -6(x + -7) + -9

Reorder the terms:
32 + 6x = -6(-7 + x) + -9
32 + 6x = (-7 * -6 + x * -6) + -9
32 + 6x = (42 + -6x) + -9

Reorder the terms:
32 + 6x = 42 + -9 + -6x

Combine like terms: 42 + -9 = 33
32 + 6x = 33 + -6x

Solving
32 + 6x = 33 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
32 + 6x + 6x = 33 + -6x + 6x

Combine like terms: 6x + 6x = 12x
32 + 12x = 33 + -6x + 6x

Combine like terms: -6x + 6x = 0
32 + 12x = 33 + 0
32 + 12x = 33

Add '-32' to each side of the equation.
32 + -32 + 12x = 33 + -32

Combine like terms: 32 + -32 = 0
0 + 12x = 33 + -32
12x = 33 + -32

Combine like terms: 33 + -32 = 1
12x = 1

Divide each side by '12'.
x = 0.08333333333

Simplifying
x = 0.08333333333

See similar equations:

| W/8-27=6 | | 1/2(y-8)=1/4y=2 | | 10b+31=7b+43 | | X^2+11x+82=0 | | 1-25b^2=0 | | -5.2y+7.2y=-8.4 | | 2v=25-3v | | 6=1-2v+5 | | 6y+3=6y-8 | | -13x-15=-54 | | -3(5-x)-(x-2)=7x-2 | | 11d+9d=20 | | 12=3u+72 | | 3z^3+7z^2+27z+63=0 | | 12x+12=10x-10 | | 0.86=In(y) | | 3/7x-4=12 | | 3/7x-4=16 | | 3x+18x^2-81x=0 | | -4(x-1)=10x-10 | | 4x-14/x-3 | | Y=80-2x | | 4v+28=v+51 | | 3x+7=7x+13 | | 3tgx+4=tgx+4 | | 18/x-3=6 | | 2x^2+6=166 | | 15x^2-2=123 | | 2w=10w-32 | | 7x-11=5x-15 | | 90=-6+2(-4x+10) | | 0=2x^2-6x+24 |

Equations solver categories